We will be different forever: A qualitative study of changes of body image in women with breast cancer - Cernikova, Kristyna A; Kracmarova, Lucie Kluzova; Pesoutova, Markéta; Tavel, Peter (BMC public health, 2024)
OBJECTIVE: This study explores the experience of body-image changes throughout the trajectory of breast cancer. METHODS: We conducted qualitative in-depth interviews with 53 women (n = 53) representing diverse age groups, with a mean age of 48.61 years (SD = 13.12), from various regions across the Czech Republic. The interviews were audio/video recorded and divided into two phases. The initial phase consisted of a narrative part, followed by a semi-structured interview. Thematic analysis was employed to identify and explore the topics that held significant importance to the participants. RESULTS: This research investigated how body image and emotional responses evolve in women with breast cancer during various stages of the illness. Throughout the breast cancer journey, women undergo diverse body image changes, with some of them being described as particularly traumatic, such as hair loss and preventive operations. The effects of breast cancer extend beyond physical scars, influencing femininity and womanhood in the long run. The experience of womanhood is marked by visible and non-visible effects that persist for years after treatment. CONCLUSION: Study has provided valuable insights into the emotional journey that women experience during breast cancer diagnosis, treatment, and survivorship. The illness trajectory framework has proven to be a valuable tool for understanding the complexities of body image concerns and the emotional implications faced by breast cancer patients. By acknowledging the significance of body image issues and providing targeted interventions, healthcare providers can improve the psychosocial well-being and overall quality of life for breast cancer survivors. Further research in this area is needed to develop and refine supportive interventions that address the unique challenges women face during their breast cancer journey. Ultimately, by fostering a sensitive and comprehensive approach to care, we can empower women to navigate their breast cancer journey with greater resilience and confidence.
Keywords: Qualitative Research; Humans; lidé středního věku; Female; Aged; dospělí; senioři; lidé; kvalitativní výzkum; Interviews as Topic; Adult; Breast Neoplasms; ženské pohlaví; představa o vlastním těle; Middle Aged; Czech Republic; nádory prsu; Body Image; Česká republika; rozhovory jako téma